Analisis upaya mengatasi perselisihan keluarga dalam masalah kewarisan masyarakat Lombok Tengah - Bungarusvianto, Teguh; Jumharim, Jumharim; Arifin Munir, Zainal (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
This research aims to understand how the Praya Religious Court handles inheritance disputes in Central Lombok district. The phenomenon that occurs is often a dispute between family members involving third parties from the surrounding community. This research was conducted using qualitative methods. Data was collected directly from participants or through observing behavior in their natural situation, which was then reinforced with primary and secondary data sources. Primary data sources in this research are internal and external informants from the Praya Religious Court. Based on the results of the research on the main causes of family conflict in inheritance disputes, the first is that all inheritances have never been divided and are controlled unilaterally by some heirs. Secondly, the inheritance has been divided within the family but not in accordance with the provisions. The best and preferred settlement effort is through out-of-court (non-litigation) deliberation institutions, either privately between family members. Settlement can also involve the help of religious leaders, traditional leaders, and government leaders to reach a fair and harmonious agreement. The best effort to resolve family conflicts in inheritance disputes in the Central Lombok community is through out-of-court deliberation institutions (non-litigation). The conclusion of the research is that the settlement of inheritance disputes by religious courts is optimally carried out through non-litigation deliberations, both directly between family members and with the help of religious leaders, officials of the Religious Affairs Office, Customary Chiefs, Hamlet Heads, and Village Heads.